The Impact of Foreign Retail and Wholesale Stores on Traditional Wholesale Stores in Nonthaburi Province, Thailand - Cheevapruk, Supitcha (Information Management and Business Review, 2012)
The entrance of foreign retail and wholesale businesses in Thailand started some ten years ago and led to the closure of many Thai wholesale stores. The objective of this study is to determine the needs of Thai wholesalers in the Nonthaburi area and to identify suitable strategies for relevant managers to be able to compete with contemporary commercial strategies of the foreign enterprises. A total of 114 of the 120 Thai traditional wholesale stores in Nonthaburi were surveyed by questionnaire and results were analyzed by statistical means. It was found that low price strategy, location of store and full cycle service strategies were the principal approaches employed by the managers of the foreign wholesale and retail stores. Tesco Lotus was the foreign venture with the greatest impact on the Thai environment. With respect to managerial approach, it was found that Thai traditional wholesale stores should try to build stronger relationships with customers and regularly search for new markets. Employee performance should also be taken into consideration to some extent. Other issues of importance included the presentation of the store and visual merchandising, as well as transparency in management systems and the need for well–organized financial and accounting systems and their proper control.